ECOLINGUISTIC STUDY OF CONSERVATION NEWS TEXTS IN INDONESIAN MASS MEDIA - Yuniawan, Tommi (Sanata Dharma University, 2018)
This study aims to describe the study of ecolinguistics in the conservation news text in Indonesian mass media. The study of ecolinguistics examines discourse texts pertaining to the environment. The environmental discourse with all its embodiments (oral text, written text, images and internet) is called green texts. Green texts can be found in the consolidated news text in the mass media. This text contains a language expression of conservation events or issues relating to the vision of a conservation-oriented university. The research used descriptive qualitative method. This research data in the form of lingual unit of news fragment of conservation news sourced from mass media of Indonesia which is relatively many. Methods of data collection are done by referring the method, literature study method, and documentation method. Furthermore, the data were analyzed by using the method of comparison and contrast. Based on the results of the analysis and discussion, it is concluded that in the conservation news text in Indonesian mass media, it is found that ecolexicon in the texts are in the form of (a) base word, (b) derivative words, (c) noun phrases, (d) verbal phrases, and (e) adjective phrases. The results of this study are expected to contribute theoretically and practically to the field of linguistics, language learning, journalism, and public policy.Â DOI:Â https://doi.org/10.24071/ijhs.2018.010203